Correlation of Stature and Foot Length among Medical Students from Southern Parts of India - Potdar, Ashutosh B; Kiran, G T; Shrikanthan, G; Potdar, Pallavi A; Mittal , Anuj (Journal of Indian Academy of Forensic Medicine, 2016)
Stature is one of the primary characteristics of identification of human beings. The main concern of the Forensic investigations in mass disasters is to establish personal identity of unknown and dismembered human remains. Like other body parts, the foot of a person exhibits biological correlation with height. The present study is a cross sectional study undertaken with aim to find out the correlation of percutaneous measurement of foot length with the height of a person and to estimate the stature from foot length among a group of medical students. The sample of the study included 305 (142 males and 163 females) medical under graduate students of age group between 18 to 22 years who were born and brought up in Southern Parts of India (Puducherry, Tamil Nadu, Karnataka, Kerala and Andhra Pradesh). Maximum foot length and height were measured by Vernier calliper and stadiometer respectively. Predictive equations using linear regression were derived. The correlation between stature and foot length was found to be statistically significant. Regression equation derived was Stature = 58.145 + 4.421 x Foot Length. The accuracy of stature determination by this method is reported to be 71%.